Soybean farmers in Kenya poised to Make Millions - Dashiell, Kenton E. (International Center for Tropical Agriculture, 2011)
The N2Africa Soil Improvement project by CIAT-TSBF, which works with nitrogen-fixing soil bacteria to increase soybean productivity, provided several crop production materials to over 4000 farmers in Western Kenya between March and April 2011. The materials included 42 demonstration kits, 4084 packets of inoculant, 3875 kg of soybean and climbing bean seed, 8200 kg of fertilizer, and 2750 copies of extension materials. The work of the project is further supplemented with the participation of the private and the NGO sectors in Kenya including fertilizer blending companies, bio-fertilizer producers, manufacturing companies, and extension organizations. For example, MEA Fertilizer, one of the partner organizations, is providing nitrogen-fixing inoculants and fertilizers to the key implementing farmer groups, who will plant a total of 18,986 kg of seed resulting in an estimated harvest of 380 metric tons of soybean grain by August 2011.